Extreme changes in the dayside ionosphere during a Carrington-type magnetic storm - Tsurutani, B. T.; Verkhoglyadova, Olga P.; Mannucci, Anthony J.; Lakhina, G. S.; Huba, Joseph D. (My University, 2012)
It is shown that during the 30 October 2003 superstorm, dayside O+ ions were uplifted to DMSP altitudes (~850 km). Peak densities were ~9 × 105 cm−3 during the magnetic storm main phase (peak Dst = −390 nT). By comparison the 1–2 September 1859 Carrington magnetic storm (peak Dst estimated at −1760 nT) was considerably stronger. We investigate the impact of this storm on the low- to mid-latitude ionosphere using a modified version of the NRL SAMI2 ionospheric code. It is found that the equatorial region (LAT = 0° ± 15°) is swept free of plasma within 15 min (or less) of storm onset. The plasma is swept to higher altitudes and higher latitudes due to E × B convection associated with the prompt penetration electric field. Equatorial Ionization Anomaly (EIA) O+ density enhancements are found to be located within the broad range of latitudes ~ ± (25°–40°) at ~500–900 km altitudes. Densities within these peaks are ~6 × 106 oxygen ions-cm−3 at ~700 km altitude, approximately +600% quiet time values. The oxygen ions at the top portions (850–1000 km) of uplifted EIAs will cause strong low-altitude satellite drag. Calculations are currently being performed on possible uplift of oxygen neutrals by ion-neutral coupling to understand if there might be further significant satellite drag forces present.
Keywords: Ionosphere (mid latitude); Electric field; Coronal mass ejection (CME); Flares; Ionosphere (equatorial)